Strategi Komunikasi Dakwah (Studi Analisis Dakwah Tradisonal dengan Inovasi Digital) - Deni Irawan (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the traditional da'wah communication strategy using digital innovation as an effort to increase the effectiveness of delivering da'wah messages in the modern era. The phenomenon of shifting da'wah patterns from conventional to digital is the main focus of this study, considering the development of information technology that influences people's communication patterns. This study uses a qualitative approach with an analytical study type. Primary data sources were obtained through in-depth interviews with da'wah figures, da'wah institution administrators, and digital da'wah activists, while secondary data were obtained from documentation in the form of lecture recordings, social media content, and related literature. Data collection techniques were carried out through interviews, observations, and documentation studies. Data analysis used the Miles and Huberman interactive model, namely data reduction, data presentation, and drawing conclusions. The validity of the data was checked using source triangulation techniques, technical triangulation, member checks and peer debriefing. The results of the study show that traditional da'wah communication strategies combined with digital innovation are able to increase audience reach, strengthen da'wah interactions, and enrich da'wah message delivery methods. This research is expected to contribute to the development of da'wah strategies that are more adaptive and relevant to the needs of contemporary society.